2015
DOI: 10.1115/1.4028165
|View full text |Cite
|
Sign up to set email alerts
|

A Selective Multiclass Support Vector Machine Ensemble Classifier for Engineering Surface Classification Using High Definition Metrology

Abstract: The surface appearance is sensitive to change in the manufacturing process and is one o f the most important product quality characteristics. The classification o f workpiece sur face patterns is critical fo r quality control, because it can provide feedback on the manu facturing process. In this study, a novel classification approach fo r engineering surfaces is proposed by combining dual-tree complex wavelet transform (DT-CWT) and selective ensemble classifiers called modified matching pursuit optimization w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…From Fig. 7, some findings are obtained (1) The proposed CK based method performs significantly better than OK when systematic machining errors exist. For instance, in Case 1 the flatness error estimation assessment ratio is between 0.7 and 0.75 for OK while between 0.85 and 0.95 for CK.…”
Section: Simulationmentioning
confidence: 93%
See 2 more Smart Citations
“…From Fig. 7, some findings are obtained (1) The proposed CK based method performs significantly better than OK when systematic machining errors exist. For instance, in Case 1 the flatness error estimation assessment ratio is between 0.7 and 0.75 for OK while between 0.85 and 0.95 for CK.…”
Section: Simulationmentioning
confidence: 93%
“…Since TIN and IDW methods do not have estimation variance error, criteria MSPE and RMSPE cannot be obtained for them. From Table 4, some findings are obtained (1) The unmeasured point can be estimated by nearest measured points using traditional interpolation methods like TIN and IDW, but the result of estimation is less precise than the Kriging methods. The indices of ME and MSE for TIN and IDW are larger than that for the Kriging methods.…”
Section: Comparison Analysis With Other Spatial Interpolation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that chip serration causes microwaves on machined surfaces, which increases machined surface roughness. In addition, Du and Fei conducted a series of studies on surface topography classification and measurement in conventional milling [14][15][16][17]. However, there has been no relevant research involving UPRFC.…”
Section: Introductionmentioning
confidence: 98%
“…SVM classifies a sample as a positive or negative Vapnik, 2000). However, most problems in the real world are usually multiclass problems (Du, Liu, & Xi, 2015;Huang, Zhang, Zeng, & Bushel, 2013;Pathak & Sunkaria, 2014;YJlmaz & KJlJkçJer, 2013). For multiclass problems, there are more than two classes, and a sample is classified as one class among many classes.…”
Section: Introductionmentioning
confidence: 99%